UNDERSTANDING TOWARDS TRADERS' BUSINESS ETHICS OF ISLAM: A STUDY OF ACEH DEALERS IN KUALA LUMPUR - Muhammad Abdul Samad; Nor Aini binti Ali (Islam Futura, 2014)
Islamic business ethics is one that should be the practice of Muslim traders, because Islam promotes this method for fairness, honesty and the benefit of people. Ethical values of Islam must be known and understood by all Muslim traders to avoid cheating that may oppress customers. This study uses qualitative methods and obtains data from the interviewers and observations. The study found that the majority of Aceh traders has understood the ethical businessmen in Islam which can be seen from the activities they are doing in each of its business practices. Aceh dealers are usually honest, fair, occupying commitment, hardworking and making efforts in business.